2013
DOI: 10.1007/s12039-013-0523-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of vanadium and pyridine in heteropolycompounds for selective oxidation of alcohols with hydrogen peroxide

Abstract: and a hybrid pyridine-modified heteropolyacid with Keggin structure for selective oxidation of alcohols to ketones or aldehydes using aqueous hydrogen peroxide and acetonitrile as solvent. Performance of these different catalysts in 1-phenylethanol oxidation was studied. Influence of reaction temperature, amount of catalyst and hydrogen peroxide and reaction time on the yield of acetophenone was investigated to obtain optimal reaction conditions. Oxidation ability of the catalyst depended on the number of vana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Under optimized reaction conditions, no oxidation took place in the presence of pyridinum chloride (Table , entry 11), but 70% conversion was obtained after 3 hours of reaction using the MoO 3 as catalyst (Table , entry 12). It is suggested that due to the existing electronic interaction between the pyridinum ion and [Mo 8 O 26 ] 4− component, the Lewis acid sites (Mo‐center) are effectively modified in this hybrid structure . A delay time in the oxidation of benzyl alcohol in the presence of 2,6‐di‐tert‐butyl‐4‐methylphenol as a radical scavenger also is a proof that our system proceeds via the free radical chain mechanism.…”
Section: Resultsmentioning
confidence: 71%
“…Under optimized reaction conditions, no oxidation took place in the presence of pyridinum chloride (Table , entry 11), but 70% conversion was obtained after 3 hours of reaction using the MoO 3 as catalyst (Table , entry 12). It is suggested that due to the existing electronic interaction between the pyridinum ion and [Mo 8 O 26 ] 4− component, the Lewis acid sites (Mo‐center) are effectively modified in this hybrid structure . A delay time in the oxidation of benzyl alcohol in the presence of 2,6‐di‐tert‐butyl‐4‐methylphenol as a radical scavenger also is a proof that our system proceeds via the free radical chain mechanism.…”
Section: Resultsmentioning
confidence: 71%
“…[18][19][20][21][22][23][24][25] Moreover, overoxidation of the sulfoxides to sulfones is a common problem during the oxidation of sulfides [26,27] that has garnered attention from the synthetic community. [12,14,[46][47][48][49] In recent years, owing to the redox properties of ceria, various types of ceria-based catalysts including cerium (IV) triflate, [50] ammonium cerium (IV) nitrate, [51] immobilized cerium alkyl phosphonate [52] and heterobimetallic cerium (IV) oxo clusters [53] are also widely used in selective oxidation of sulfides. From an economical and environmental viewpoint, an acceptable process involving hydrogen peroxide (H 2 O 2 ) as a terminal oxidant in the presence of a catalyst would be at particular interest, [28,29] since hydrogen peroxide produces water as by-product and it is worth mentioning that a controlled partial oxidation is also dramatically easier than the most of other oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Complete characterization of the catalysts PMo 11 V and Py 3 -PMo 11 V was reported in a previous work [17,18]. Here, we present some relevant analysis of the catalysts in order to verify their characteristics.…”
Section: Characterization Methodsmentioning
confidence: 78%
“…The synthesis and full characterization of the PMo 11 V and Py 3 -PMo 11 V catalysts were reported in a previous work [17,18]. The SEM-EDAX analysis of heteropolyacid catalysts shows a homogeneous distribution of V, Mo, and P according to the expected percent atomic ratios.…”
Section: Catalyst Characterizationmentioning
confidence: 84%